Kodokushi as the Impact of Juggernaut of Modernity in Japanese Hyper-Aging Era - Elsy, Putri; Wirawan, I. B.; Saptandari, Pinky (MOZAIK HUMANIORA, 2024)
This article aims to describe the phenomenon of kodokushi (lonely death) among the elderly in Japan’s hyper-aging society as a negative impact of modernity. The research is analyzed through Anthony Giddens’ juggernaut of modernity perspective. The juggernaut is a walking machine (giant panzer) with extraordinary power, which we can steer to a certain extent but is also likely to lose control and tear itself to pieces. The results show that the phenomenon of lonely death (kodokushi) in the elderly reflects the uncontrollable juggernaut of modernity. Changes in family structure, the decline in birth rates, and cultural values that Japanese people hold cause kodokushi to remain high in Japan, especially among the elderly. Elderly people who live alone without traditional family or community ties live in social isolation. In the context of Giddens' Juggernaut of Modernity, the juggernaut has lost control. The phenomenon of kodokushi reflects complex challenges. Many older people experience isolation and loneliness due to a lack of strong social ties. Culturally, the ingrained culture of not wanting to inconvenience others (meiwaku wo kakutakunai) in Japanese society is a barrier to overcoming kodokushi. Addressing this phenomenon requires holistic efforts from the government, social institutions, and society. Although efforts to overcome kodokushi have been made, understanding and dealing with these complexities is crucial in Japan's hyper-aging society.